Improvement in Sarf (morphology) competency through gamification at Miri national religious secondary school (SMKAMi) - Zailani, Suhaila; Abu Bakar, Kaseh; Mustapha, Nik Farhan; Zainal, Hakim; Nawawi, Zulkifli; Jamsari, Ezad Azraai (Human Resource Management Academic Research Society, 2019)
Learning through the gamification method can bring the students directly closer to real experience. Students have the opportunity to improve their ability to remember, increase sensitivity to interaction process and possess the capability to objectively analyse a situation. The purpose of this article is to introduce a type of gamification to strengthen Sarf (morphology), in addition to tracking improvement in Sarf competency after implementing the gamification method at Miri National Religious Secondary School (SMKAMi) in the 2017 Malaysian Certificate of Examination (SPM). This research uses a qualitative method and data was taken mainly from the Arabic Morphology Diagnostic Test (UDMA) and through the instrument of interview using WhatsApp application (voice message or voice recording). Two teachers were involved in the interview session: Head of Arabic Language Committee and an Arabic language teacher who teaches Form 5. The data obtained were transcribed in writing and descriptively analysed. Research findings show an improved achievement in Arabic language subject of the 2017 SPM by 1.09 with Average Grade of Subjects (GPMP) of 3.64 compared to 4.73 of the previous year. Research results show that the gamification method can resolve student weakness in Sarf, especially in remembering the verb and noun patterns and their derivatives, besides increasing student engagement, creating fun and fostering a positive attitude through game activity. The implications of this research will open the space for research on gamification designs appropriate for strengthening Nahu and Sarf with a high prospect for their application in the context of Arabic language education.